PENGARUH BLENDING KOPI ROBUSTA DAN ARABIKA TERHADAP KUALITAS SEDUHAN KOPI - Suwarmini, Ni Nyoman; Mulyani, Sri; Lani Triani, I.G. Ayu (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2017)
This study aims to determine the effect of blending of robusta and arabica coffee on the quality of brewed coffee and determine the blending ratio that produces the best coffee brew. This study used a Completely Randomized Design (RAL) with six treatments of blending ratio of robusta and arabica coffee (0: 100; 20:80; 40:60; 60:40; 80:20; and 100: 0)%. Data were analyzed variance and if there was effect of treatment on observed variables followed by Ducan test. The results showed that blending treatment had a very significant effect on pH, caffeine, juice, and holistic acceptance of coffee (overalls). Based on the holistic favorite level of coffee, the best treatment is obtained from blending arabica : robusta coffee ratio (100: 0; 80:20; 60:40 and 40: 60)%, yielding coffee brewed with pH 5.26-5, 01, the kadar sari content 25,67 - 24,94%, caffeine content 2,16 - 1,50% Keywords : blending, robusta coffee, arabica coffee and brewed coffee